Chatbot As An Artificial Intelligence Program In Autonomous Learning In Nursing Students At A University In Piura, 2023 - Sandoval Peña, Jose Manuel (2023)
Objective: To determine the effects of chatbot as an artificial intelligence (AI) program on autonomous learning (ML) of nursing students at a private university in Piura, 2023. Method: quantitative, applied, experimental and pre-experimental approach. The population consisted of students of the Nursing Study Program and a sample of 32 students from the ninth cycle. A pretest and posttest were applied and 16 sessions were executed in the program. Results: according to the self-learning dimension with the pretest, 90.6% were placed in the low autonomy level, with the posttest 100% were located in the autonomous level. In self-regulation, the posttest presented 96.9%, establishing them at the medium level and low autonomy, with the posttest 100% are at the autonomous level. In metacognition, the pretest indicated that 78.1% were at the low level and at the posttest 100% were at the autonomous level. Conclusion: It was demonstrated that there is a significant influence of the program on the development of autonomous learning, accepting the alternative hypothesis.